PELAKSANAAN PERJANJIAN BAGI HASIL TANGKAPAN LAUT ANTARA PEMILIK KAPAL NELAYAN DAN NELAYAN PENGGARAP DI KECAMATAN KEPULAUAN KARIMATA KABUPATEN KAYONG UTARA - AGUS LIANI NIM. A1011151124 (Fakultas Hukum Universitas Tanjungpura, 2023)
AbstractThe background of this research problem is based on the profit-sharing agreement made between the ship owner and the ship's crew, based on an oral agreement that has occurred long ago. The distribution of the results obtained after going to sea to the parties varies greatly depending on the habits of the local community and also depending on the agreement of the parties. The agreement creates a legal relationship between the ship owner and the ship's crew and in that relationship, each party has reciprocal rights and obligations.The title of this research is the Implementation of Marine Catch Sharing Agreements between Fishing Boat Owners and Cultivating Fishermen in Karimata Islands District, North Kayong Regency. The formulation of the problem in this research is